Application of Markov chain to share price movement in Nigeria (1985–2019) - Charles O. Manasseh; Nnah M. Iroha; Kingsley I. Okere; Ifeoma C. Nwakoby; Ogochukwu C. Okanya; Nnenna Nwonye; Onuselogu Odidi; Oliver I. Inyiama (Future Business Journal, 2022)
Abstract The study evaluates the movement of share prices in the Nigerian stock market. Markov chain approach provides a successful analysis and prediction of time-series data (1985–2019) which reflects Markov dependency. The probability $$α$$ α and $$β$$ β was estimated, and the expectation of the monthly increase (E(I)) and decrease (E(D)) of the share price index was obtained as 5 months and 3 months, respectively. The steady-state probabilities π1 and π2 were obtained as 0.335 and 0.665, respectively, independent of the initial conditions. The results observed that as the years rolled, the monthly share prices continued to increase due to increased activity in the stock market. In addition, further investigation shows that share price movement and stock market performance influence economic performance. Based on the findings, the Nigerian government and the market authorities should initiate policies that reduce arbitragers' ability to forecast and beat the markets to forestall investors' confidence. Hence, investor property rights protection, discouragement of insider trading, and ensuring that local or domestic investors are enlightened about the stock market and the inherent benefits in Nigeria will enhance stock market efficiency and growth.